Application of Counseling with a Cognitive Behavior Therapy Approach to Handling Inferiority Complex in Students - Kandoko, Isabella Vannessa Pranata; Nawangsari, Nur Ainy Fardana (Jurnal Indonesia Sosial Sains, 2025)
An inferiority complex is a psychological condition experienced when an individual feels inferior, helpless, and views themselves as a failure despite having adequate abilities. This condition is often experienced by students or individuals during emerging adulthood, where individuals are in a transitional phase characterized by personal, academic, and social demands. This study aims to determine the effectiveness of applying counseling with a cognitive behavior therapy (CBT) approach in overcoming an inferiority complex. The research approach used was an experiment with a single-case experimental design method. The subjects in this study were DA, a third-semester student at the Faculty of Psychology, University X, who experienced inferiority complex problems based on assessments conducted using interviews, intelligence tests, and perfectionism scales. The results showed a significant decrease in the symptoms of inferiority complex experienced by the subjects. The subjects began to be able to recognize and challenge their irrational thoughts, showed increased self-confidence, and were more adaptive in dealing with failure and academic pressure. These findings confirm that counseling with a cognitive behavior therapy (CBT) approach can be declared effective as a psychological intervention approach in overcoming inferiority complex in students.